Analysis of early reading difficulties in second grade students at SD N Karangtengah I Giricahyo, Purwosari, Gunungkidul - Novia Lestari; Biya Ebi Praheto; Dinar Martia Azizah (Psychology, Evaluation, and Technology in Educational Research, 2025)
The study aimed to describe the early reading difficulties experienced by second-grade students at SD N Karangtengah I Giricahyo, Purwosari, Gunungkidul, identify the contributing factors, and formulate solutions to address them. The research employed a qualitative descriptive method using observation, reading tests, interviews with teachers and students, and documentation. Data analysis followed the Miles and Huberman model, which included data collection, reduction, presentation, and conclusion drawing. The findings indicated that early reading difficulties were characterized by slow letter recognition, errors in distinguishing similar letters, and weak phoneme-letter association skills, which affected reading fluency and text comprehension. The Egra test revealed that 37.50% of students were in the low category, while only 12.50% were in the very good category. The contributing factors included low motivation and interest in reading, lack of parental support, and technical barriers such as spelling difficulties and letter differentiation. Additionally, ineffective teaching methods worsened the situation. The proposed solutions included regular reading activities, the implementation of the phonics method to enhance phonemic skills, additional tutoring, and active parental involvement in supporting children's literacy. Schools were also encouraged to provide literacy facilities such as reading corners and integrate literacy activities before lessons. The synergy between teachers, parents, and schools was key to improving students' early reading abilities.